2022
DOI: 10.1002/jmr.2961
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of immunogenic peptide constructs comprising multiple human leukocyte antigen restricted dengue virus envelope epitopes

Abstract: Dengue virus (DENV) is endemic in 100 countries with the ability to impact nearly 50% of world population. DENV envelope (E) protein is responsible for viral attachment to host cells and has been target of various countermeasure development efforts. The current study focuses on a consensus computational approach to identify cross-reactive, immunogenic DENV-2 E peptides displaying promiscuity with a wide array of human leukocyte antigen (HLA) molecules. Four conserved peptides (FP-1, FP-2, FP-3 and FP-4) contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Docking scores of most of the epitopes and peptides were found to be higher than or in the range of scores of naturally bound peptides, indicating the favorable presentation of peptides to HLA class I and II MHC to activate T cell immune response. The result is in agreement with previous studies on peptide-HLA interactions of Dengue [17]. Ismail and colleagues [23] also identified experimentally determined epitopes from the ViPR database and demonstrated their interaction with HLA molecules.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Docking scores of most of the epitopes and peptides were found to be higher than or in the range of scores of naturally bound peptides, indicating the favorable presentation of peptides to HLA class I and II MHC to activate T cell immune response. The result is in agreement with previous studies on peptide-HLA interactions of Dengue [17]. Ismail and colleagues [23] also identified experimentally determined epitopes from the ViPR database and demonstrated their interaction with HLA molecules.…”
Section: Discussionsupporting
confidence: 90%
“…All three peptides displayed lower coverage for North America. There are similar studies [17,61] where the population coverage for some peptides was shown to be lower in North America than in other continents. The population coverage of peptides could be limited due to the absence of orthohantavirus-bindingdominant HLA alleles in North America in the peptides selected in our study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Further, the CABS‐Docking network server was used to simulate the interaction between thrombus‐binding peptides and fibrin. [ 16,54 ]…”
Section: Methodsmentioning
confidence: 99%
“…Further, the CABS-Docking network server was used to simulate the interaction between thrombus-binding peptides and fibrin. [16,54] The Synthesis of Bi Nanoparticles (NPs): Bi NPs were prepared from Bi(NO 3 ) 3 •5H 2 O by high temperature vacuum method. [55] Bi(NO 3 ) 3 •5H 2 O of 970 mg were dissolved in 1-dodecanethiol in a three-neck flask with magnetic stirring.…”
Section: Methodsmentioning
confidence: 99%